Understanding the Issue of Taxpayer Compliance and Knowledge Gaps - Hutahuruk, Marice Br; Ridwan, Muhammad; Hairudin, Hairudin; Prayetno, Muhammad Pringgo; Renaldo, Nicholas (Nexus Synergy: A Business Perspective, 2024)
This research uniquely focuses on cognitive barriers, emphasizing the need for taxpayer education and simplified communication of tax laws. The novelty lies in presenting taxpayer education as a strategic tool to enhance compliance, thus shifting the focus from a compliance model based on fear to one based on understanding and support. This research adopts a qualitative approach, utilizing semi-structured interviews and focus group discussions (FGDs) to collect data from various stakeholders, including individual taxpayers, tax consultants, and tax authorities. This research concludes that improving taxpayer compliance requires addressing the knowledge barriers that exist in the tax system. Simplified tax regulations, better access to tax information, and enhanced taxpayer education can significantly reduce unintentional non-compliance. Tax authorities should invest in educational programs and provide clearer, more user-friendly tax guidelines. Future research could extend this study by incorporating quantitative measures to assess the relationship between tax knowledge and compliance rates.